2013
DOI: 10.3389/fnins.2013.00081
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins and translational regulation in axons and growth cones

Abstract: RNA localization and regulation play an important role in the developing and adult nervous system. In navigating axons, extrinsic cues can elicit rapid local protein synthesis that mediates directional or morphological responses. The mRNA repertoire in axons is large and dynamically changing, yet studies suggest that only a subset of these mRNAs are translated after cue stimulation, suggesting the need for a high level of translational regulation. Here, we review the role of RNA-binding proteins (RBPs) as loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 130 publications
0
63
0
Order By: Relevance
“…The transport of mRNAs into axons and their translation within axons can be regulated by extracellular stimuli (4).…”
Section: Introductionmentioning
confidence: 99%
“…The transport of mRNAs into axons and their translation within axons can be regulated by extracellular stimuli (4).…”
Section: Introductionmentioning
confidence: 99%
“…The local translation of transcripts represents a very important mechanism contributing to synaptic plasticity and arborization (Till et al 2011;Jung et al 2012), axonal growth (Campbell and Holt 2001;Hörnberg and Holt 2013), as well as axonal viability and neuronal development (Taylor et al 2013). In this regard, numerous studies showed that disruption of SMN function causes presynaptic abnormalities and abnormal synaptic transmission with poorly arborized axons at the neuromuscular junction (NMJ) terminals (Jablonka et al 2007;Kariya et al 2008;Kong et al 2009), suggesting that SMN might be directly involved in the regulation of axonal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Additional, but less frequent, cases have been reported with point mutations in the FMR1 gene (De Boulle et al 1993;Lugenbeel et al 1995;Wang et al 1997) leading to classic features of FXS. The gene encodes for the Fragile Mental Retardation protein (FMRP), an RNAbinding protein with four RNA-binding domains affecting different aspects of mRNA metabolism including transport, stability, and translation Doyle and Kiebler 2012;Wang et al 2012;Darnell and Klann 2013;Hornberg and Holt 2013;Rajan 2014). The absence of FMRP leads to a deregulated protein translation resulting in excessive accumulation of certain proteins and reduction of others (for review, see Bagni et al 2012).…”
Section: From Genetic Causes To Model Systems For Fxsmentioning
confidence: 99%